2016
DOI: 10.1371/journal.pone.0150262
|View full text |Cite
|
Sign up to set email alerts
|

Blood Transcriptomic Markers in Patients with Late-Onset Major Depressive Disorder

Abstract: We investigated transcriptomic markers of late-onset major depressive disorder (LOD; onset age of first depressive episode ≥ 50 years) from the genes expressed in blood cells and identified state-dependent transcriptomic markers in these patients. We assessed the genes expressed in blood cells by microarray and found that the expression levels of 3,066 probes were state-dependently changed in the blood cells of patients with LOD. To select potential candidates from those probes, we assessed the genes expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 61 publications
0
37
0
Order By: Relevance
“…In preclinical studies, female rodents with bilateral ovariectomies (OVXs) are frequently used as a model of menopause in women (Cho et al, 2004; Liu et al, 2004). In addition, previous reports, including ours, suggested that OVX rodents are vulnerable to stress and exhibit behavioral abnormalities similar to animal models of depression when subjected to chronic mild stress (CMS) (Lagunas et al, 2010; Miyata et al, 2016; Nakagawasai et al, 2009). Therefore, OVX rodents subjected to CMS are likely a reasonable animal model of depression during menopause.…”
Section: Introductionmentioning
confidence: 50%
See 3 more Smart Citations
“…In preclinical studies, female rodents with bilateral ovariectomies (OVXs) are frequently used as a model of menopause in women (Cho et al, 2004; Liu et al, 2004). In addition, previous reports, including ours, suggested that OVX rodents are vulnerable to stress and exhibit behavioral abnormalities similar to animal models of depression when subjected to chronic mild stress (CMS) (Lagunas et al, 2010; Miyata et al, 2016; Nakagawasai et al, 2009). Therefore, OVX rodents subjected to CMS are likely a reasonable animal model of depression during menopause.…”
Section: Introductionmentioning
confidence: 50%
“…It has been reported that the expression levels of genes associated with protein biosynthesis and energy production are altered in the prefrontal cortex of the post-mortem brains of MDD patients (Klempan et al, 2009; Sibille et al, 2004). It has also been reported that OVX induces vulnerability to stress in female rodents (Lagunas et al, 2010; Miyata et al, 2016; Nakagawasai et al, 2009). Therefore, the dysregulated pathways associated with protein biosynthesis and energy production that were observed in the mPFC in the mice in the current study may be associated with the development of stress vulnerability.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We demonstrated the utility of the SATIC methodology for the detection of transcriptomic biomarkers 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 using the 40-mer-and 39-mer-length folding parts 50 of the RNA transcripts of the genes encoding the cell death-inducing DNA fragmentation factor-α (DFFA)-like effector C (CIDEC) 51 and adenosine diphosphate (ADP)-ribosylation factor related protein 1 (ARFRP), 52 i.e., CidR and ArfR, as target and nontarget RNAs, respectively ( Figure S11). Owing to the high G4-selective emission of ThT-HE, the positivity could clearly be recorded and displayed even with a general-purpose digital camera and without using fluorescence imaging systems with software programs for coloring and/or adjustment of the range of the fluorescence scale.…”
Section: Resultsmentioning
confidence: 99%